Notification of crop varieties and registration of germplasm - Shinde, M.S. (The Indian Journal of Genetics and Plant Breeding, 2016)
CSV 30F is a kharif forage sorghum single cut variety derived through pedigree method from a cross NSS 223 x NARI 111. It was identified for single cut forage by 43rd Annual Sorghum Group Meeting held at Hyderabad on 21st to 23rd April 2013 at National level comprising the states of Haryana, Punjab, Rajasthan, Gujarat, Uttarakhand and Uttar Pradesh of Zone-I and Maharashtra and Karnataka and Tamil Nadu of ZoneII. The variety was subsequently notified by Central Sub-committee on Crop Standards, Notification and Release of Varieties for Agricultural crops vide notification number S. O. 1919 (E) dated 31/7/2014. CSV 30F is tall variety with an average plant height around 267 cm. It flowers in 76 days after germination. Leaves are green in colour with white midrib. Earheads are semi loose and oval in shape with round, pearly white grain colour. The grains are one fourth covered by glumes. It has a better forage quality such as protein (8.07%, 9.67 q/ha), IVDMD (50.2%), digestible dry matter (57.6 q/ha) and low HCN (56.5 ppm) contents